Analysis of properties of inertia regulator of thrust control system of liquid rocket engine - M. M. Dron; A. B. Yakovlev (Омский научный вестник: Серия "Авиационно-ракетное и энергетическое машиностроение")
The quality of the flight task of a space rocket system is determined among other things by the accuracy of maintaining and regulating the thrust of the rocket engine. Improving the accuracy and reducing errors in the engine mode control system will reduce the cost of space launches or allow you to put a large payload into orbit. The article presents a mathematical model of a controller with an inertial booster of a liquid-propellant rocket engine, identifies parameters and values that affect its accuracy, and considers measures to reduce static error